1991
DOI: 10.1111/j.1432-1033.1991.tb16377.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of the gene encoding the soluble cytochrome b562 of Escherichia coli

Abstract: The gene for the soluble cytochrome b562 from Escherichia coli B has been cloned on a SalI fragment. The analysis of the gene reveals the presence of a leader sequence in front of the sequence encoding the mature protein. Expression of cytochrome b562 using the lac‐promoter produced the protein to a level of 3–5% of total protein. This over‐production enables employment of a simple, high‐yield purification protocol to obtain homogeneous cytochrome b562. Spectroscopic and N‐terminal sequence analyses of the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…The reporter system is based on E. coli cytochrome b 562 , which is encoded by the cybC gene (27) and is a water-soluble, monomeric, periplasmic cytochrome of unknown specific function. It is a very stable 12-kDa four-helix bundle protein containing one non-covalently bound protoheme IX (14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reporter system is based on E. coli cytochrome b 562 , which is encoded by the cybC gene (27) and is a water-soluble, monomeric, periplasmic cytochrome of unknown specific function. It is a very stable 12-kDa four-helix bundle protein containing one non-covalently bound protoheme IX (14).…”
Section: Resultsmentioning
confidence: 99%
“…A 0.5-kb KpnI-BamHI fragment of the E. coli cybC gene (bp 250 to 703; accession no. S74736) (27) was amplified by using pNS207 as the template and Pwo polymerase (Boehringer Mannheim) in the PCR. The buffer contained 10 mM Tris-HCl (pH 8.85), 2.5 mM KCl, 50 mM (NH 4 ) 2 SO 4 , and 5 mM MgSO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Purification of wild-type and mutant cyt b562 was performed essentially as described previously Nikkila et al, 1991) with some modifications as indicated below.…”
Section: Expression and Purification Of Cytochromes B562mentioning
confidence: 99%
“…The protein contains an N-terminal leader sequence that is cleaved upon transport across the inner periplasmic membrane, where its biological function is believed to be electron transfer (Nikkila et al, 1991). The structure of cyt b562 was originally solved by X-ray crystallography at 2.5 A resolution (Mathews et al, 1979;Lederer et al, 1981) and recently refined to 1.4 A (F.S.…”
mentioning
confidence: 99%
See 1 more Smart Citation